An Interactive and Multimodal Virtual Mind Map for Future Workplace - Kuťák, David; Doležal, Milan; Kerous, Bojan; Eichler, Zdenek; Vašek, Jiří; Liarokapis, Fotis (Frontiers in ICT, 2019)
Traditional types of mind maps involve means of visually organizing information. They can be created either using physical tools like paper or post-it notes or through the computer-mediated process. Although their utility is established, mind maps and associated methods usually have several shortcomings with regards to effective and intuitive interaction as well as effective collaboration. Latest developments in virtual reality demonstrate new capabilities of visual and interactive augmentation, and in this paper, we propose a multimodal virtual reality mind map that has the potential to transform the ways in which people interact, communicate, and share information. The shared virtual space allows users to be located virtually in the same meeting room and participate in an immersive experience. Users of the system can create, modify, and group notes in categories and intuitively interact with them. They can create or modify inputs using voice recognition, interact using virtual reality controllers, and then make posts on the virtual mind map. When a brainstorming session is finished, users are able to vote about the content and export it for later usage. A user evaluation with 32 participants assessed the effectiveness of the virtual mind map and its functionality. Results indicate that this technology has the potential to be adopted in practice in the future, but a comparative study needs to be performed to have a more general conclusion.